2008
DOI: 10.1002/elps.200700400
|View full text |Cite
|
Sign up to set email alerts
|

Novel open tubular CEC with tentacle‐type polymer stationary phase functionalized by phenylalanine

Abstract: A novel stationary phase with tentacle-type polymer chains with epoxy groups was fabricated for open tubular CEC. The fabrication procedure of the stationary phase included pretreatment of capillary inner wall, silanization, and glycidyl methacrylate (GMA)-grafted polymerization. The influence of initiator concentration and polymerization time on the resulting polymer stationary phase was studied by measuring EOF mobility and hydrophobicity of the prepared capillary column. SEM showed that the capillary inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The results suggested that the capillary with monolithic layer exhibited less separation efficiency than the capillary with monolithic column. This might be due to a lower phase ratio for interactions with analytes in the OTcapillary CEC, which could cause broadening and skewing of solute bands, thereby lower resolutions in separations [24]. Meanwhile, capillary columns with monolithic stationary phases had greater phase ratios than OT-capillary columns [25][26][27], and thus, resulting in a high separation efficiency for five analytes.…”
Section: Cec Mode For the Separation Of Vitamin Bmentioning
confidence: 98%
“…The results suggested that the capillary with monolithic layer exhibited less separation efficiency than the capillary with monolithic column. This might be due to a lower phase ratio for interactions with analytes in the OTcapillary CEC, which could cause broadening and skewing of solute bands, thereby lower resolutions in separations [24]. Meanwhile, capillary columns with monolithic stationary phases had greater phase ratios than OT-capillary columns [25][26][27], and thus, resulting in a high separation efficiency for five analytes.…”
Section: Cec Mode For the Separation Of Vitamin Bmentioning
confidence: 98%
“…However, the OT capillary column still bears the primary shortcoming of low phase ratio that impeding its wide application in chromatography separation. In order to overcome the above limitation, several attempts, such as etching the capillary [1], porous polymer layer [2][3][4][5], sol-gel techniques [6,7] and nanoparticle coating [8][9][10] have been made to increase the surface area, therefore to greatly improve the OT-CEC performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we prepared a few tentacle-type polymermodified capillary columns for open tubular capillary electrochromatographic separations of neutral analytes, amino acids, and proteins [18][19][20]. Both capillary inner surface area and ligand capacity were largely increased by coating the tentacle-type polymers, which can provide high analyte adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%